Graphitization of banana peel – synergistic effect of Ca and other elements of the biomass on carbon structure transformation - Muhammad Jamshaid Shabbir; Barbara Liszka; Magdalena Szubka; Mirosława Pawlyta; Maciej Zubko; Jan Ilavsky; Karolina Jurkiewicz (Biomass and Bioenergy, 2026)

Lornoxicam Loaded Transethosomal Gel: Formulation, Box-Behnken Optimization, Ex-Vivo and In-Vivo Characterization - Minahal Munir; Sarah Ahmad; Talha Jamshaid; Huma Hameed; Muhammad Zaman; Usama Jamshaid; Muhammad Jamshaid; Sara Khalid; Heba A. Gad (Journal of Pharmaceutical Innovation, 2026)

Dental caries beyond eradication: microbiome centered and equilibrium driven therapeutic strategies - Maryam Jabeen; Huma Hameed; Areej Abdul Razzaq; Muhammad Jamshaid; Muhammad Amish Shakeel; Tehreem Mushtaq (Archives of Microbiology, 2026)

Formation of Adsorbable Organic Halogens (AOX) from Chlorination and Chloramination in Full-scale Drinking Water Production - Muhammad Jamshaid Ashiq; Anna Andersson; Henrik Kylin; Teresia Svensson; Michael Gonsior; David Bastviken (Water, Air, & Soil Pollution, 2026)
Formation of disinfection by-products (DBPs) in drinking water production constitutes a health hazard. The total amount of DBPs is usually measured as adsorbable organic halogens (AOX). We determined AOX in samples from four full-scale drinking water treatment plants (DWTPs) in Sweden using different types of raw waters and treatments. Raw water, water before and after chlorination or chloramination and tap water were sampled on five occasions during one year without applying quencher to stop chlorination reactions. Coagulation removed most (> 95%) of the AOX present in the raw water at one DWTP. Sand filtration used in all DWTPs had no clear effect on AOX levels already present in the intake water, while some AOX formation occurred during Ultraviolet (UV) treatment. AOX increased dramatically at all DWTPs during both chlorination and chloramination due to the formation of DBPs. When not using any quencher similar AOX formation was found in both chlorine and chloramine treated water, showing that substantial DBP formation occurred upon chloramination even if few regulated DBPs were detected in these DWTPs in previous assessments. Because the contribution of non-DBP AOX varies between sources and treatment processes, ∆AOX, i.e., AOX in final water subtracted by AOX prior to chemical disinfection, should be considered in DBP assessments.

Retraction notice to “Investigation on synthesis of ternary g-C3N4/ZnO–W/M nanocomposites integrated heterojunction II as efficient photocatalyst for environmental applications” [Environ. Res. Volume 217, 15 January 2023, 114621] - Misbah Malik; Thomas Len; Rafael Luque; Sameh M. Osman; Emilia Paone; Muhammad Imran Khan; Muhammad Ahmad Wattoo; Muhammad Jamshaid; Aqsa Anum; Aziz ur Rehman (Environmental Research, 2025)

Recent advances in nanocatalysis for clean energy and carbon neutral applications - Jamshaid Rashid; Ayesha Arif; Pir Muhammad; Ming Xu; Rajeev Kumar (Fuel, 2025)

Protease activated receptor inhibitors in rheumatoid arthritis: a new frontier in treatment - Tayyaba Rana; Huma Hameed; Ana Cláudia Paiva-Santos; Muhammad Jamshaid; Muneeba Anwar (Inflammopharmacology, 2025)

Magnetically recyclable Mn and Co doped r-GO based LaFeO3 nano-composite for tuning the optical and solar light driven photo-catalytic applications - Shahid Iqbal; Muhammad Jamshaid; Firdous Bibi; Najla AlMasoud; Taghrid S. Alomar; Rashid Iqbal; Qasim Raza; Ambreen Kalsoom (Journal of Water Process Engineering, 2025)

Evaluation of Genotype × Environment Interaction and Yield Stability of Cotton (Gossypium hirsutum L) Genotypes Under Heat Stress Conditions - Iram Sharif; Saba Aleem; Jamshaid Ali Junaid; Muqadas Aleem; Khazina Jamshaid; Huma Saleem; Muhammad Rizwan; Shahid Munir Chohan; Saqib Sohail; Saba Akram; Muhammad Zeeshan; Ghulam Sarwar (Journal of Crop Health, 2025)

Exploring the potential of nanomedicine for gene therapy across the physicochemical and cellular barriers - Huma Hameed; Hafiz Shoaib Sarwar; Komel Younas; Muhammad Zaman; Muhammad Jamshaid; Ali Irfan; Maha Khalid; Muhammad Farhan Sohail (Functional & Integrative Genomics, 2024)

Dynamic nexus among fossil fuels utilization, economic growth, and urbanization: a tri-regional selected countries analysis - Muhammad Aamir; Jamshaid ur Rehman (Environmental Science and Pollution Research, 2024)

A Comprehensive Review of Hydrogel-Based Drug Delivery Systems: Classification, Properties, Recent Trends, and Applications - Huma Hameed; Saleha Faheem; Ana Cláudia Paiva-Santos; Hafiz Shoaib Sarwar; Muhammad Jamshaid (AAPS PharmSciTech, 2024)

Field response and molecular screening of European wheat germplasm against powdery mildew at the Himalayan region of Pakistan - Aamir Iqbal; Zia Ur Rehman; Muhammad Rameez Khan; Amir Muhammad Khan; Shahid Ullah Khan; Muhammad Arif; Javaid Iqbal; Mujeeb Ur Rehman; Minhaj Ali; Muhammad Qasim; Imran Ali; Zakir Hussain Facho; et al. (Journal of Applied Genetics, 2023)

Enhancement in anaerobic biogas conversion by visible light photocatalytic Pre-treatment of rice husk with indium vanadate decorated titanium dioxide nanocomposite - Jamshaid Rashid; Talha Tufail Bhatti; Muhammad Hassan; M.A. Barakat; Rajeev Kumar; Ming Xu (Fuel, 2023)

RETRACTED: Investigation on synthesis of ternary g-C3N4/ZnO–W/M nanocomposites integrated heterojunction II as efficient photocatalyst for environmental applications - Misbah Malik; Thomas Len; Rafael Luque; Sameh M. Osman; Emilia Paone; Muhammad Imran Khan; Muhammad Ahmad Wattoo; Muhammad Jamshaid; Aqsa Anum; Aziz ur Rehman (Environmental Research, 2023)

Efficient photocatalytic degradation of Rhodamine B dye using solar light-driven La˗Mn co-doped Fe2O3 nanoparticles - Sobia Maqbool; Adeel Ahmed; Arif Mukhtar; Muhammad Jamshaid; Aziz Ur Rehman; Saima Anjum (Environmental Science and Pollution Research, 2023)

Foliar Application of Silicon Improved Physiological Indicators, Yield Attributes, and Yield of Pearl Millet (Pennisetum glaucum L.) Under Terminal Drought Stress - Allah Wasaya; Jamshaid Hassan; Tauqeer Ahmad Yasir; Muhammad Ateeq; Muhammad Ali Raza (Journal of Soil Science and Plant Nutrition, 2022)

Strategic combination of metal–organic frameworks and C3N4 for expeditious photocatalytic degradation of dye pollutants - Ome Parkash Kumar; Muhammad Ahmad; Muhammad Altaf Nazir; Aqsa Anum; Muhammad Jamshaid; Syed Shoaib Ahmad Shah; Aziz Rehman (Environmental Science and Pollution Research, 2022)

Transfersomes: a Revolutionary Nanosystem for Efficient Transdermal Drug Delivery - Muhammad Waseem Akram; Humzah Jamshaid; Fiza Ur Rehman; Muhammad Zaeem; Jehan zeb Khan; Ahmad Zeb (AAPS PharmSciTech, 2021)

Biological control of strawberry crown rot, root rot and grey mould by the beneficial fungus Aureobasidium pullulans - Mudassir Iqbal; Maha Jamshaid; Muhammad Awais Zahid; Erik Andreasson; Ramesh R. Vetukuri; Johan A. Stenberg (BioControl, 2021)
Utilization of biocontrol agents is a sustainable approach to reduce plant diseases caused by fungal pathogens. In the present study, we tested the effect of the candidate biocontrol fungus Aureobasidium pullulans (De Bary) G. Armaud on strawberry under in vitro and in vivo conditions to control crown rot, root rot and grey mould caused by Phytophthora cactorum (Lebert and Cohn) and Botrytis cinerea Pers, respectively. A dual plate confrontation assay showed that mycelial growth of P. cactorum and B. cinerea was reduced by 33–48% when challenged by A. pullulans as compared with control treatments. Likewise, detached leaf and fruit assays showed that A. pullulans significantly reduced necrotic lesion size on leaves and disease severity on fruits caused by P. cactorum and B. cinerea . In addition, greenhouse experiments with whole plants revealed enhanced biocontrol efficacy against root rot and grey mould when treated with A. pullulans either in combination with the pathogen or pre-treated with A. pullulans followed by inoculation of the pathogens. Our results demonstrate that A. pullulans is an effective biocontrol agent to control strawberry diseases caused by fungal pathogens and can be an effective alternative to chemical-based fungicides.

Natural and semisynthetic polymers blended orodispersible films of citalopram - Yasser Shahzad; Maimoona Maqbool; Talib Hussain; Abid Mehmood Yousaf; Ikram Ullah Khan; Tariq Mahmood; Muhammad Jamshaid (Natural Product Research, 2020)

Evaluation of engine performance and exhaust emission characteristics in a diesel engine using isobutanol— Calophyllum inophyllum biodiesel—diesel ternary blends - Azham Alwi; Nurin Wahidah Zulkifli; Nazatul Liana Sukiman; Ashraf Yusoff; Zulfattah Zakaria; Muhammad Jamshaid; Muhammad Harith Hasnul; Muhammad Syahir Amzar (Environmental Science and Pollution Research, 2019)

Evaluating gas chromatography with a halogen-specific detector for the determination of disinfection by-products in drinking water - Anna Andersson; Muhammad Jamshaid Ashiq; Mohammad Shoeb; Susanne Karlsson; David Bastviken; Henrik Kylin (Environmental Science and Pollution Research, 2019)

Correction to: An efficient protocol for the synthesis of highly sensitive indole imines utilizing green chemistry: optimization of reaction conditions - Bushra Nisar; Syeda Laila Rubab; Abdul Rauf Raza; Sobia Tariq; Sana Jamshaid; Ayesha Sultan; Muhammad Nawaz Tahir (Molecular Diversity, 2019)